Tunable and giant valley-selective Hall effect in gapped bilayer graphene - Yin, Jianbo (2022)
Berry curvature is analogous to magnetic field but in momentum space and is commonly present in materials with nontrivial quantum geometry. It endows Bloch electrons with transverse anomalous velocities to produce Hall-like currents even in the absence of a magnetic field. We report the direct observation of in situ tunable valley-selective Hall effect (VSHE), where inversion symmetry, and thus the geometric phase of electrons, is controllable by an out-of-plane electric field. We use high-quality bilayer graphene with an intrinsic and tunable bandgap, illuminated by circularly polarized midinfrared light, and confirm that the observed Hall voltage arises from an optically induced valley population. Compared with molybdenum disulfide (MoS2), we find orders of magnitude larger VSHE, attributed to the inverse scaling of the Berry curvature with bandgap. By monitoring the valley-selective Hall conductivity, we study the Berry curvature's evolution with bandgap. This in situ manipulation of VSHE paves the way for topological and quantum geometric optoelectronic devices, such as more robust switches and detectors.